Get sleep or get stumped: sleep behaviour in elite South African cricket players during competition - McEwan, K.; Davy, J.; Christie, C. J.-A. (Journal of Sports Sciences, 2020)
Despite evidence supporting the positive affect sleep has on sport performance, there is limited application of sleep research in cricket. This study investigated the sleep behaviours of 26 elite South African cricket players (28.6 ± 4.0 years) during home and away competition. Players completed an altered version of the Core Consensus Sleep Diary every morning post-travel, pre-match and post-match. Linear mixed model regression was used to compare differences in sleep between time-periods, venues and formats. Spearman`s correlations (rs) assessed the relationship of match performance and sleep. Post-match total sleep time (06:31 ± 01:09) was significantly (p < 0.05) shorter compared to post-travel (07:53 ± 01:07; g = 1.19) and pre-match (08:43 ± 01:03; g = 1.98). Post-travel sleep onset latency and sleep efficiency were significantly shorter (-20; g = 1.35) and higher (+10.4%; g = 0.74) at home than away respectively. Longer sleep onset latencies and shorter total sleep times were significantly associated with poorer One-Day International (rs = -0.57) and Test (rs = 0.59) batting performances respectively. The poor post-match sleep behaviour, and the sleep and performance correlations, provide motive for future interventions to focus on recovery and the use of sleep monitoring as a competitive advantage